2023
DOI: 10.1021/jasms.2c00333
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Behavior of Galactofuranosides upon Collisional Fragmentation: A Multistage High-Resolution Ion Mobility Study

Abstract: Carbohydrates are ubiquitous in nature but are among the least conserved biomolecules in life. These biopolymers pose a particular challenge to analytical chemists because of their high diversity and structural heterogeneity. In addition, they contain many isomerisms that complicate their structural characterization, notably by mass spectrometry. The tautomerism of the constitutive subunits is of particular interest. A given cyclized monosaccharide unit can take two forms: a most common 6membered ring (pyranos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…More recently, we further demonstrated that it was generally possible to identify oligosaccharidic fragments by comparison with matching reference IMS profiles even for reputedly unstable structures like furanosideswith the exception of one very specific case where we observed an isomerization of the fragments. However, we proved that the isomerization in that specific case occurred during the fragmentation stage (but independently from the collision energy), and not during the drift of the ion in the IMS stage . Overall, our previous results indicate that mobility profiles of oligosaccharidic fragments are robust enough to envision a sequencing strategy based on those profiles.…”
Section: Introductionsupporting
confidence: 56%
“…More recently, we further demonstrated that it was generally possible to identify oligosaccharidic fragments by comparison with matching reference IMS profiles even for reputedly unstable structures like furanosideswith the exception of one very specific case where we observed an isomerization of the fragments. However, we proved that the isomerization in that specific case occurred during the fragmentation stage (but independently from the collision energy), and not during the drift of the ion in the IMS stage . Overall, our previous results indicate that mobility profiles of oligosaccharidic fragments are robust enough to envision a sequencing strategy based on those profiles.…”
Section: Introductionsupporting
confidence: 56%
“…The strategy implemented in this study capitalized on recent works on the synthesis of the four possible regioisomers of Gal f -Man p and Gal p -Man p disaccharides. 20–22 In each case, the synthesis of a -family derivatives (Gal f family) and b -family compounds (Gal p one) followed a similar sequence of reactions.…”
Section: Resultsmentioning
confidence: 99%
“…To access the ring-size information in larger oligosaccharides, the fragmentation approach could be envisioned, which requires the investigation of the impact of CID on the highly flexible furanose ring. We have recently reported promising IM-MS results on the fragmentation of galactose-containing trisaccharides, where the Gal-Man disaccharide fragment retained its structure in some conditions . To validate the sequencing approach, it is thus essential to generalize the conservation of the ring-size structural features upon CID fragmentation, particularly in monosaccharide fragments.…”
Section: Introductionmentioning
confidence: 99%